Shifts in form and meaning in the translation of the subtitles of Battle Trip (배틀 트립) variety show ep 114 Trip to Bandung - Rio Abdu Rojak; Dianni Risda; Velayeti Nurfitriana Ansas (Universitas Pendidikan Indonesia (UPI), 2023)
The process of conveying meaning between two languages is called translation. This qualitative research study aims to depict changes in form and meaning during the translation of subtitles from the Korean variety show